A high-speed search engine pLink 2 with systematic evaluation for proteome-scale identification of cross-linked peptides - Zhen-Lin Chen (Nature Portfolio, 2019)
The identification of cross-linked peptides at a proteome scale for interactome analyses represents a complex challenge. Here the authors report an efficient and reliable search engine pLink 2 for proteome-scale cross-linking mass spectrometry analyses, and demonstrate how to systematically evaluate the credibility of search engines.